PECULIARITIES OF NUTRITION IN CHILDREN WITH MUCOVISCIDOSIS - E.A. Roslavtseva; T.E. Borovik; O.I. Simonova; A.S. Ignatova (Вопросы современной педиатрии, 2010)
Authors analyze a problem of digestion disorders in children with cystic fibrosis (mucoviscidosis). The basis of these disorders is chronic pancreatic insufficiency, developed as malabsorption of fat and steatorrhea, and, to a lesser degree, as disorders of assimilation of protein and starch. A correction of such disorders in infants should be performed with the use of well-balances compound combined with effective pancreatic enzymes, according to the expert’s recommendations. These measures can compensate increased energy consumption in child with cystic fibrosis, provide patient’s normal growth and development, and decrease the rate of infectious complications. Key words: infants, mucoviscidosis, nutrition.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(1):162-167)